Europe's response to the Inflation Reduction Act: achieving a net zero economy - Kreivi, Eila (Henry Stewart Talks, 2023)
European Investment Bank, Werner Hoyer, EU equity fund, US IRA, Green transition, Investment, Blended financing, Greenfield investments